Vilas urbanas de Manaus: habitação coletiva, herança cultural e lugares de memória (1900-1950) - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This dissertation presents the phenomenon of Manaus Urban Villages as collective housing experiences, built in the first half of the twentieth century. The Vilas inserted at the Historic Center of Manaus urban-facric, are morphologically distinguished by the emplacement within the blocks, in which predominates the notion of ensemble established in the architectural conception campared to surrounding buildings, and which reveal, from their materiality, processes that were part of the city's production. The relevance as a cultural heritage is demonstrated from the typological analysis of architecture and the configuration of its private and semi-public spaces, and at the same time, as receptacles of part of the collective memory of the formation of the manauara city, from the interpretation of spaces of relations. neighborhoods that remain in the present day.
Manaus urban villages: collective housing, cultural heritage and places of memory (1900-1950)
Keywords: Centro Histórico de Manaus; Tipologia arquitetônica; Herança cultural; Residencial multifamiliar; Paisagem urbana; CIÊNCIAS HUMANAS; Vilas; Habitação coletiva; Tipologia; Herança cultural; Memória